Note to the Spanish Pharmacopoeia, IX Edition: Calcium Carbonate - García Villanova, R.; Thomas, J.; Bosch, F. (Ars Pharmaceutica (Internet), 1966)
A tritimetry and complexometric technics of evaluation of calcium carbonate has been revised. We recommended a complexometric technic, using EDTA and a murexide as indicator, in order to include it in the new Spanish Pharmacopeia edition.